IPTEKS PENERAPAN PSAK NO. 23 ATAS PENJUALAN ENERGI LISTRIK PASCABAYAR DAN PRABAYAR PADA PT. PLN (PERSERO) UNIT LAYANAN PELANGGAN MANADO SELATAN - Rianto, Rifka Sharen; Mailakay, Dian Christin; Maradesa, Djeni (Universitas Sam Ratulangi, 2018)
In this study discusses the recognition or income in selling electricity in meters postpaid and prepaid in the company PT PLN (Persero) ULP Manado Selatan, where recognition and registration are in accordance with the theory of PSAK no. 23, This study uses descriptive analysis, interviews and data collection to Kariyawan. Recognition is a process of recording formally carried out by post into a financial statement account within the entity. While recording is a planning process to record bookkeeping, describes events that have occurred measuring through in a structured way in sequence.Keywords: Â Sales, Recognition, Postpaid and Prepaid Records, PSAK No. 23